2004
DOI: 10.1200/jco.2004.03.185
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Interferon in High-Risk Melanoma: The AIM HIGH Study—United Kingdom Coordinating Committee on Cancer Research Randomized Study of Adjuvant Low-Dose Extended-Duration Interferon Alfa-2a in High-Risk Resected Malignant Melanoma

Abstract: The results from this study, taken in isolation, do not indicate that extended-duration low-dose interferon is significantly better than observation alone in the initial treatment of completely resected high-risk malignant melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(84 citation statements)
references
References 25 publications
3
75
1
5
Order By: Relevance
“…Several other prospective randomized trials examined interferon-α2b at a variety of doses and treatment schedules in patients with high-risk stage II melanoma, but none has demonstrated a survival benefit. [19][20][21][22] These studies are complicated by a lack of a standardized definition of 'high-risk' , 23 different interferon-α2b doses and schedules, and in some cases include other drugs in combination. Figure 1 | Stage II melanoma immunotherapy treatment algorithm.…”
Section: Literature Review and Analysismentioning
confidence: 99%
“…Several other prospective randomized trials examined interferon-α2b at a variety of doses and treatment schedules in patients with high-risk stage II melanoma, but none has demonstrated a survival benefit. [19][20][21][22] These studies are complicated by a lack of a standardized definition of 'high-risk' , 23 different interferon-α2b doses and schedules, and in some cases include other drugs in combination. Figure 1 | Stage II melanoma immunotherapy treatment algorithm.…”
Section: Literature Review and Analysismentioning
confidence: 99%
“…The greatest benefit was observed in patients with micrometastases detected by the sentinel node biopsy, while the patients with palpable lymph nodes did not have any benefits (Eggermont et al, 2008). Several studies with small doses of IFN showed the effect to DFS Pehamberger et al, 1998;Cameron et al, 2001;Kirkwood et al, 2000;Hancock et al, 2004), of which, only one showed significant importance for OS . On the other hand, the WHO-16 study, which tested low doses of IFN in duration of 3 years in patients in stadiums IIIB and IIIC, did not show any significant effect to DFS or OS (Cascinelli et al, 2001).…”
Section: Radiotherapy Of Melanoma In Pregnancymentioning
confidence: 99%
“…They speculate that this could be a result of patients having died of other causes, but there have been no data presented to support this. The general 540 Letter to the Editor The Oncologist ® consensus of the melanoma field [2][3][4][5][6] is that these trials demonstrated a small improvement in time to relapse but that individually, in a pooled analysis by Kirkwood and colleagues [7], in an independent review [4], and in a meta-analysis [3], these trials have not provided evidence for an improvement in overall survival.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%